Тематика военных переводных книг в СССР (1920-1930-е годы) (Библиосфера)
The article deals with the thematic repertoire of military translated books published in the USSR in the 20's and 30's of the XXth century. Analyzed are the direction of translation activities in military publishing , the article provides statistical analysis of the revealed translated military works.